2019
DOI: 10.1186/s12891-019-2600-6
|View full text |Cite
|
Sign up to set email alerts
|

Pedi-IKDC or KOOS-child: which questionnaire should be used in children with knee disorders?

Abstract: Background The Pedi International Knee Documentation Committee (IKDC) and Knee Injury and Osteoarthritis Outcome Score (KOOS) child are validated questionnaires for children with knee disorders. The aim of this study was to translate these questionnaires in Dutch and to recommend which questionnaires should – based on their psychometric properties – be used in clinical practice. Methods The English Pedi-IKDC and KOOS-Child were translated by the forward-backward procedu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
62
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(71 citation statements)
references
References 24 publications
7
62
1
Order By: Relevance
“…There are consistent reports of high convergent and divergent construct validity, with the IKDC Subjective Knee Evaluation Form more strongly correlated with the Short Form 36 (SF‐36) physical subscales and component summary than with the mental subscales and component summary . Construct validity is acceptable in the pediatric form and improved over the KOOS‐Child form . Studies have shown the IKDC Subjective Knee Evaluation Form score to be highly correlated with the Cincinnati Knee Rating System, pain visual analog scale (VAS), Oxford 12 Questionnaire, WOMAC, Lysholm score, and SF‐36 physical component, physical function, and bodily pain subscales .…”
Section: International Knee Documentation Committee Subjective Knee Ementioning
confidence: 87%
“…There are consistent reports of high convergent and divergent construct validity, with the IKDC Subjective Knee Evaluation Form more strongly correlated with the Short Form 36 (SF‐36) physical subscales and component summary than with the mental subscales and component summary . Construct validity is acceptable in the pediatric form and improved over the KOOS‐Child form . Studies have shown the IKDC Subjective Knee Evaluation Form score to be highly correlated with the Cincinnati Knee Rating System, pain visual analog scale (VAS), Oxford 12 Questionnaire, WOMAC, Lysholm score, and SF‐36 physical component, physical function, and bodily pain subscales .…”
Section: International Knee Documentation Committee Subjective Knee Ementioning
confidence: 87%
“…It was also the reason to exclude studies from the systematic review update. Nine additional studies 15,53,58,62,67,68,121,124,125 were added following the updated search, and hypotheses were all confirmed. The former conclusion of conflicting evidence for hypothesis testing changed to strongly positive.…”
Section: Validitymentioning
confidence: 99%
“…Only three studies 56,82,126 had sufficient methodological quality to be assessed. In the updated review seven additional studies were included 15,53,58,67,68,121,124,125 and the updated review result suggests strong positive findings. The Swedish IKDC-SKF had poor methodological quality for measurement error, due to small sample size, but the result of the testing is consistent with previous findings.…”
Section: Reliabilitymentioning
confidence: 99%
See 2 more Smart Citations